(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
This research was finding out the learners’ writing performance through point-counterpoint strategy by using video blog. The aims of this research were: 1) to find out whether or not the point-counterpoint strategy through video blog elevate the learners’ writing performance, and 2) to find out the learners’ interest toward the use of video blog through point-counter-point strategy in teaching writing performance. Pre experimental design is carried out by the researcher in this research. The sample of this research was XI IPA2 (33 learners). This sample was taken by the random sampling technique. This research applied two kinds of instruments were writing test and questionnaire in this research.The result of this research shows that the learners’ performance is better writing after they taught by using point-counter-point strategy through video blog at SMA Negeri 3 Polewali Mandar. It was proved by the mean score of the post-test was higher than the pre-test (81.96>68.03). So, the researcher stated that H0 was rejected and H1 was accepted. And the researcher also found that the eleventh-grade learners at SMA Negeri 3 Polewali Mandar were interested in teaching writing performance. It was proved by the mean score of the questionnaire was 80.21 and it was classified in the interesting category.